PNPLA3 I148M Variant Impairs Liver X Receptor Signaling and Cholesterol Homeostasis in Human Hepatic Stellate Cells - Francesca Virginia Bruschi; Thierry Claudel; Matteo Tardelli; Patrick Starlinger; Fabio Marra; Michael Trauner (Hepatology Communications, 2019)
The patatin‐like phospholipase domain‐containing protein 3 (PNPLA3) I148M variant predisposes to hepatic steatosis and progression to advanced liver injury with development of fibrosis, cirrhosis, and cancer. Hepatic stellate cells (HSCs) drive the wound healing response to chronic injury, and lack of liver X receptor (LXR) signaling exacerbates liver fibrogenesis by impairing HSC cholesterol homeostasis. However, the contribution of the I148M variant to this process is still unknown. We analyzed LXR expression and transcriptional activity in primary human HSCs and overexpressing LX‐2 cells according to PNPLA3 genotype (wild type [WT] versus I148M). Here we demonstrate that LXRα protein increased whereas LXR target gene expression decreased during in vitro activation of primary human HSCs. Notably, LXRα levels and signaling were reduced in primary I148M HSCs compared to WT, as displayed by decreased expression of LXR target genes. Moreover, reduced expression of cholesterol efflux and enzymes generating oxysterols was associated with higher total and free cholesterol accumulation whereas endogenous cholesterol synthesis and uptake were diminished in I148M HSCs. Luciferase assays on LXR response element confirmed decreased LXR transcriptional activity in I148M HSCs; in contrast the synthetic LXR agonist T0901317 replenished LXR functionality, supported by adenosine triphosphate‐binding cassette subfamily A member 1 (ABCA1) induction, and reduced collagen1α1 and chemokine (C‐C motif) ligand 5 expression. Conversely, the peroxisome proliferator‐activated receptor gamma (PPARγ) agonist rosiglitazone had only partial effects on the LXR target gene ABCA1, and neither diminished expression of proinflammatory cytokines nor increased de novo lipogenic genes in I148M HSCs. Conclusion: As a consequence of reduced PPARγ activity, HSCs carrying I148M PNPLA3 show impaired LXR signaling, leading to cholesterol accumulation. The use of a specific LXR agonist shows beneficial effects for diminishing sustained HSC activation and development of liver fibrogenesis.